The impact of mothers’ health education on the prevalence of acute respiratory infections in children - Günay, Osman; Öztürk, Ahmet; Öztürk, Yusuf (The Turkish Journal of Pediatrics, 1994)
In this study, the effects of educating mothers on acute respiratory infections were investigated in Hacilar district of Kayseri, a province in Central Anatolia. The intervention group included 69 children and the control group 57 children between the ages of 0 and 4 years. The children in both groups were checked for symptoms of acute respiratory infections (ARI) in January 1990 and 1991, before and after intervention. The intervention consisted of 30 minutes of face-to-face education of mothers regarding ARI prevention and treatment. In addition, the numbers of clinic visits by children for acute respiratory infections before and after intervention were compared. The prevalence of acute respiratory infections decreased from 49.3% to 27.5% in the intervention group and from 43.9% to 38.6% in the control group. The decrease in the prevalence of acute respiratory infections in the intervention group differed significantly, from that of the control group. On the other hand, clinic visits by the intervention group for acute respiratory infections increased significantly